2008
DOI: 10.1111/j.1745-5871.2008.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural Youth Migration Trends in Australia: an Overview of Recent Trends and Two Inland Case Studies

Abstract: Much of what has been written on the topic of Australian rural youth migration trends and processes has often proceeded from data‐free, or data‐poor grounds. In this context, this paper analyses recent trends in youth (15 to 24 years of age) migration for a temporally‐consistent set of Statistical Divisions (SDs) in inland rural Australia, and for local government areas within the Northern Tablelands and Slopes and Ranges of northern New South Wales and the Western Australian Central Wheatbelt. The paper finds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…On the flip side, other regions are faced with managing the impact of declining populations (Collits 2008;Pritchard and McManus 2000). For instance, the impact of rural youth outmigration and the consequent shortage of human capital for local labour markets and community activities is a key challenge for future development in some regions (Argent and Walmsley 2008;Dufty-Jones et al 2013;Tonts and Atherley 2005).…”
Section: Borders In a Mobile Worldmentioning
confidence: 99%
“…On the flip side, other regions are faced with managing the impact of declining populations (Collits 2008;Pritchard and McManus 2000). For instance, the impact of rural youth outmigration and the consequent shortage of human capital for local labour markets and community activities is a key challenge for future development in some regions (Argent and Walmsley 2008;Dufty-Jones et al 2013;Tonts and Atherley 2005).…”
Section: Borders In a Mobile Worldmentioning
confidence: 99%
“…Not all young people who move out from a rural local government area (or other administrative spatial unit) are lost to the broader region. Argent and Walmsley () revealed that many young people that left their home communities within the Western Australian central wheatbelt and the New South Wales Northern Tablelands during the 1990s actually relocated elsewhere within their respective ‘home’ region rather than flocking to the city.…”
Section: Demographic Change In Australia's Productivist Heartlandsmentioning
confidence: 99%
“…The issue of how to retain young people in rural and regional areas of Australia has been a significant concern for communities in recent decades. Rates of youth loss from rural regions of Australia have increased over the past twenty years, as ‘young people are more likely to search out capital cities than the rest of the population’ (Argent and Walmsley , p. 139). This migration is attributed to the changing nature of the economy as a primary factor, and the associated socio‐economic decline felt by many rural areas as industries fold (Argent and Walmsley ).…”
Section: Introductionmentioning
confidence: 99%